Systematic reviews of controlled trials in general and oral health care - Marinho, Valeria C.C (2015)
Systematic reviews have been established as an influential branch of clinical epidemiology and health services research, with hundreds of systematic reviews of controlled trials published in the health care literature each year. The most obvious manifestation of this trend is the Cochrane Collaboration, an international organization that aims to prepare and disseminate rigorous systematic reviews of the effects of health care interventions. The potential of systematic reviews to inform decisions about practice and policy in general and oral health care and to bring more developments in the realm of clinical trial research remains substantial. The information from high quality systematic reviews of controlled trials that now exists should inform health care decisions and further research in dentistry